2020
DOI: 10.7554/elife.63266
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the DNA binding landscape and gene regulatory network of p63 and p53

Abstract: The transcription factor p53 is the best-known tumor suppressor, but its sibling p63 is a master regulator of epidermis development and a key oncogenic driver in squamous cell carcinomas (SCC). Despite multiple gene expression studies becoming available, the limited overlap of reported p63-dependent genes has made it difficult to decipher the p63 gene regulatory network. Particularly, analyses of p63 response elements differed substantially among the studies. To address this intricate data situation, we provid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 114 publications
(211 reference statements)
1
49
0
Order By: Relevance
“…ChIP-qPCR analysis confirmed that p53 binds to two sites in RFX7 intron1 in U2OS, HCT116, and RPE-1 cells (Figure 2D ), and the binding is specific as shown by its dependence on p53 availability (Figure 2E ). Notably, we identified high-confidence p53 responsive elements (p53RE) that underlie the two p53 binding sites ( 70 ), and data from the GeneHancer collection ( 71 ) indicate that both p53 binding sites in RFX7 intron1 overlap with enhancer regions that are associated with RFX7 expression ( Supplementary Figure S1B ). Similar to our results from U2OS cells (Figure 1D and E ), PDCD4 , PIK3IP1 , MXD4 , and PNRC1 were induced upon Nutlin-3a treatment in HCT116 and RPE-1 cells in a p53 and RFX7-dependent manner, while CDKN1A was not affected by RFX7 depletion (Figure 2F ).…”
Section: Resultsmentioning
confidence: 99%
“…ChIP-qPCR analysis confirmed that p53 binds to two sites in RFX7 intron1 in U2OS, HCT116, and RPE-1 cells (Figure 2D ), and the binding is specific as shown by its dependence on p53 availability (Figure 2E ). Notably, we identified high-confidence p53 responsive elements (p53RE) that underlie the two p53 binding sites ( 70 ), and data from the GeneHancer collection ( 71 ) indicate that both p53 binding sites in RFX7 intron1 overlap with enhancer regions that are associated with RFX7 expression ( Supplementary Figure S1B ). Similar to our results from U2OS cells (Figure 1D and E ), PDCD4 , PIK3IP1 , MXD4 , and PNRC1 were induced upon Nutlin-3a treatment in HCT116 and RPE-1 cells in a p53 and RFX7-dependent manner, while CDKN1A was not affected by RFX7 depletion (Figure 2F ).…”
Section: Resultsmentioning
confidence: 99%
“…typically up-regulated by both siblings (Fischer, 2017;Riege et al, 2020). Together, these data suggest that the view of Np63 functioning as a potent negative regulator of p53 can be rejected and replaced with a context-dependent model where Np63 functions as either a trans-activator or a repressor depending on cell type and binding location.…”
Section: P53 and P63 -Dueling Rivals?mentioning
confidence: 99%
“…Transcriptome analyses revealed that p63 and p53-regulated genes show only very little overlap (Gallant-Behm et al, 2012), which was inconsistent with Np63 functioning as a negative regulator of its siblings. A broad metaanalysis of ChIP-seq and transcriptomic data corroborated that p63 and p53 regulate largely non-overlapping gene sets, and argue that Np63 is more likely to activate than to repress its target genes (Riege et al, 2020). While genome-wide data revealed an essentially exclusive trans-activator function for p53 (Allen et al, 2014;Fischer et al, 2014Fischer et al, , 2016aSullivan et al, 2018;Sammons et al, 2020), a trans-repressor function could not be ruled out for Np63 (Yang et al, 2006;Riege et al, 2020).…”
Section: P53 and P63 -Dueling Rivals?mentioning
confidence: 99%
See 1 more Smart Citation
“…Specific GOF mechanisms have been ascribed to p53 mutant in PDAC progression, including the deregulation of the other p53 family member p73 [ 41 43 ] in a molecular axis involving the transcriptional factor NF-Y [ 44 ]. Conversely, the other p53 family member, p63 [ 45 48 ], although considered a master regulator of pancreatic cancer squamous lineage specification [ 49 , 50 ] and frequently associated to p53 GOF in other models [ 51 , 52 ], has not yet emerged with a causative link in driving p53 GOF phenotype of PDAC.…”
Section: Introductionmentioning
confidence: 99%